Analisis Penerimaan Digital Library Menggunakan Technology Acceptance Model (TAM) di Universitas Hamzanwadi - Muhammad Zamroni Uska (Universitas Hamzanwadi, 2017)
The study aims to analyze acceptance digital library implementation using TAM model by analyze: (1) the effect perceived usefulness, perceived ease of use toward behavioral intention to use (2) the effect perceived usefulness, perceived ease of use, and behavioral intention to use toward actual system use. This research is a quantitative study using a survey method which was implemented at Hamzanwadi University. The population of this study was 6,548 people and the number of sample was 100 people contain of students. The sampling technique used was a cluster sampling method. While, the data collection used was a questionnaire with Likert scale. Data Analysis used Structural Equation Model (SEM). The results of this study showed that, (1) perceived ease of use had a significant influence toward behavioral intention to use (Ï 0.05), (2) perceived usefulness had not have a significant toward behavioral intention to use (Ï 0.05), (3) perceived ease of use and perceived usefulness had not have a significant toward actual system use (Ï 0.05), (4) behavioral intention to use had a significant toward actual system use (Ï 0.05).